Central Bank Independence and stock market outcomes: An event study on Borsa Istanbul - Ahmad Bash; Abdullah M. Al-Awadhi (Cogent Economics & Finance, 2023)
This study explores the importance of central bank independence on stock market outcomes. Specifically, we examine the effects of President Recep Tayyip Erdogan's decree, which removes the top officials of the Central Bank of Turkey, on Borsa Istanbul returns. We use a well-established event study methodology for five events from 20 July 2018, to 11 November 2021. The results show that the market is sensitive to the dismissal decrees in that they have positive effects on cumulative abnormal returns in the first two events, while the three events that follow have negative effects on cumulative abnormal returns. Our results support the importance of central bank independence, revealing that political intervention in central banks has a robust, positive, negative, and significant impact on stock market outcomes.
Keywords: G2; G4; 330; Borsa Istanbul; Central bank; event study methodology; stock market returns